관광지 이미지가 관광안내정보시스템 평가에 미치는 영향에 관한 연구 - 신영기; Shin, Young Kee ((사)디지털산업정보학회 논문지, 8(1), 2012)
The goal of the information system in tourism, like that of general information systems, is to create users' information needs so that the users continuously revisit the information system and retrieve the information on a regular basis. However, unlike any other information systems, the primary objective of the tourism information system is to attract tourists to the tourist sites rather than to create the users' needs for their future revisits to the information system. The tourism information system is therefore more closely related to tourists' overall tourism destination image towards the tourism destination. In this respect, the evaluation of the tourism information system should be based on tourists' overall tourism destination image towards the sites. This study examines how tourists' overall tourism destination image towards the sites affect the evaluation of the tourism information system. Specifically, I employ the tourism information system provided by Sokcho and Delone and Mclean(2003)'s the Information System Success Model in order to investigate this research question.